Resultant Force on Grains of a Real Sand Dune: How to Measure It? - R. F. Miotto; C. A. Alvarez; D. S. Borges; W. R. Wolf; E. M. Franklin (Geophysical Research Letters)
Abstract Barchan dunes usually appear under the action of one‐directional fluid flows, being found on Earth, Mars, and other celestial bodies; however, although ubiquitous in nature, understanding dune dynamics at the grain scale is challenging due to the vast number of grains involved. Here, based on subaqueous experiments using a high‐speed camera, discrete numerical computations solving the motion at the grain scale, and a special training of a convolutional neural network, we show that it is, in fact, possible to estimate the resultant force acting on the grains of a barchan dune by using images. This procedure opens new possibilities for measuring the resultant force not only on the grains of a dune, but also on relatively small elements that are imaged over time, such as rocks, boulders, rovers, and human‐built constructions photographed by satellites on terrestrial and Martian landscapes.